Retrotransposon-associated long non-coding RNAs in mice and men - Ganesh, Sravya; Svoboda, Petr (Pflugers Archiv, 2016)
Over a half of mammalian genomes is occupied by repetitive elements whose ability to provide functional sequences, move into new locations, and recombine underlies the so-called genome plasticity. At the same time, mobile elements exemplify selfish DNA, which is expanding in the genome at the expense of the host. The selfish generosity of mobile genetic elements is in the center of research interest as it offers insights into mechanisms underlying evolution and emergence of new genes. In terms of numbers, with over 20,000 in count, protein-coding genes make an outstanding >2 % minority. This number is exceeded by an ever-growing list of genes producing long non-coding RNAs (lncRNAs), which do not encode for proteins. LncRNAs are a dynamically evolving population of genes. While it is not yet clear what fraction of lncRNAs represents functionally important ones, their features imply that many lncRNAs emerge at random as new non-functional elements whose functionality is acquired through natural selection. Here, we explore the intersection of worlds of mobile genetic elements (particularly retrotransposons) and lncRNAs. In addition to summarizing essential features of mobile elements and lncRNAs, we focus on how retrotransposons contribute to lncRNA evolution, structure, and function in mammals.
Keywords: molekulární evoluce; LINE; myši; RNA dlouhá nekódující; LTR; Retroelements; zvířata; Evolution, Molecular; Humans; Mice; Retrotransposon; retroelementy; lncRNA; MaLR; RNA, Long Noncoding; SINE; lidé; Animals